Oral health literacy, knowledge, attitude, and oral health practices among college students at Jenderal Soedirman University - Fitri Diah Oktadewi; Romdlon, Mahindra Awwaludin; Laksitasari, Anindita; Hidayah, Riski Amalia (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Oral health literacy (OHL) has an important role as a medium for health promotion and efforts to prevent oral diseases through oral health behavior changes. Purpose: This study aims to determine OHL and its correlation with oral health knowledge, attitude, and oral health practice among college students. Methods: This cross-sectional study was conducted on 583 students of Jenderal Soedirman University in 2020, as the students come from different provinces in Indonesia. The Indonesian Oral Health Literacy Questionnaire was used to assess OHL. A self-designed questionnaire was used to assess oral health knowledge, attitude, and oral health practice. Results: Most students had good OHL, knowledge, and attitude toward oral health (90.7%, 84.6%, and 90.5% respectively). A Pearson correlation test showed a correlation between OHL and oral health knowledge (p = 0.044) and attitude (p = < 0.001). The Fisher exact tests showed a correlation between OHL and snacking frequency, tooth-brushing frequency, tooth-brushing time, and toothbrush changing time. The better the OHL, the better the knowledge and attitude. There was no correlation between OHL and sweet food eating frequency, the use of cleansing aids, dentist visit frequency, and the first action taken when experiencing toothache. Conclusion: OHL has a correlation with oral health knowledge and attitude. However, OHL is only related to some oral health practice indicators. The results of this study are expected to be taken into consideration when formulating strategies to improve oral health within the university.